FAO at work 2006-2007 : (Food and Agriculture Organization of the United Nations (FAO), 2007)
More people will live in cities than in countryside. From now on, population growth will be almost entirely urban. Will we be ensured a supply of safe, nutritious foods for everyone - the challenge set forth in UN Millennium Development Goal number one? What did we know about and how do we solve the problems?